GeAsSeTe/GeAsSe Pedestal Waveguides for Long-Wave Infrared Tunable on-Chip Spectroscopy - Vasileios Mourgelas; Sirawit Boonsit; James Shafto Wilkinson; Ganapathy Senthil Murugan (Photonics, 2024)
A dry-etched pedestal chalcogenide waveguide platform, designed for use in long-wave IR spectrometer applications, is demonstrated, fabricated and optically characterized. The optical layers were deposited on pre-patterned dry-etched silicon pedestals. An exceptionally low waveguide propagation loss was measured, at around 0.1 dB/cm at λ = 10 μm. The modal thermo-optic coefficient of the waveguide was experimentally estimated to be approximately 1.1 × 10−4 C−1 at λ = 1.63 μm, which is comparable to that of Si and GaAs. Waveguide spiral interferometers were fabricated, proving the potential for realization of more complex, chalcogenide-based, integrated photonic circuits. The combination of low propagation losses and a strong thermo-optic coefficient makes this platform an ideal candidate for utilization in on-chip tunable spectrometers in the long-wave IR wavelength band.